Forced Mobilization into the Red Army (1944–1945) - Tininis, Vytautas (Genocidas ir rezistencija, 2013)
Forced mobilisation into the occupying Soviet army in August 1944–May 1945 became an integral part of the terror against the population of Lithuania. The Soviet Union, which in the second half of 1944 launched a call-up of Lithuanian men to the Red Army, violated the provisions of international law specified in the 1907 Hague IV Convention on Laws and Customs of War on Land, which forbade the mobilisation of the inhabitants of an occupied territory for the occupying army or other use of the occupied population for military purposes. Article 4 of Appendix III of the convention sets forth that it is binding upon all parties regardless of whether they have ratified the convention or not. Article 45 proclaims “the occupier is forbidden to compel the inhabitants of the occupied territory to swear allegiance to the hostile power”. Since Lithuanian society viewed the Soviet Union as an occupying state, men liable for call-up evaded service in the Red Army. The position of the Lithuanian population with respect to the mobilisation, that is, the practice of evading, ignoring and hiding from the mobilisation, was conditioned by the negative attitude of the people towards the mobilisation for the alien army. This attitude already began to form during the Nazi occupation. People were aware of the fundamental provisions of the Atlantic Charter and hoped to use them in restoring the sovereignty of the state of Lithuania. The forced mobilisation for the army of the USSR in Lithuania was mainly carried out by the 4th Riflemen Division of the NKVD Internal Army and units of the border army of the USSR. The principal organisers of this military campaign in Lithuania were party leaders and heads of repressive bodies. Later the mobilisation was implemented by military commissariats. On 1 January 1945, there were 58,620 draft dodgers. The boycott of the mobilisation was a way to demonstrate resistance to the Soviet occupation. Men who had not registered at mobilisation points and were discovered in hiding were often regarded as partisans and underground fighters. They were therefore frequently treated as fighters for the armed resistance: they were threatened with prison or death, arrested (“detained”), tortured, and even executed. On the basis of archival documents, estimates have been made that in the course of military punitive operations in 1944–1945 about 5,000 defenceless people were killed. Lithuanian occupation authorities, in view of the fact that draft dodging was escalating into a massive refusal to serve, resorted to harsher policies of repression. On 12 December 1944, the Bureau of the Central Committee of the Lithuanian Communist Party (Bolsheviks) ((LCP[B] CC) adopted a resolution entitled “On Measures to Combat Deserters and Draft Dodgers of the Red Army” Order No. 064 of the People’s Commissariat of Defence mandated searching all farmsteads until all draft dodgers were detained and immediately delivered to conscription points. This and other forceful measures were actively carried out. The amnesty declared by Soviet authorities on 9 February 1945 was a failure since only 8,896 men legalised themselves by June 1945. After the end of the Soviet-German war, on 3 June 1945, Soviet authorities announced a second amnesty. From July 1944 to 1 December 1945, 36,144 persons legalised themselves (that is, they registered with Soviet agencies of repression and were issued temporary documents), of whom 27,361 were draft dodgers (according to other data, there were 34,589) and 2,423 were deserters (other data say 2,522). By 1957, 38,838 persons had legalised themselves, of whom 8,350 were partisans and 30,488 were draft dodgers, deserters, etc. Everyone who legalised himself was subjected to various repressive measures or moral coercion. More than half of these persons were forced to hide or leave Lithuania. About 10 per cent of the legalised “deserters” and 8 per cent of the legalised “draft dodgers” were imprisoned. Until December 1944, Lithuanians were sent to the so-called Lithuanian divisions. They were not placed in any other units of the Red Army. The directive of 18 October 1944 of the Red Army Mobilisation Board instructed all privates and sergeants of Lithuanian nationality to transfer from the regular army to the 50th Division by 15 November. The 16th Lithuanian Division was supplemented with new conscripts as well. No precise data exists about Lithuanian soldiers who perished in military operations while serving in the Soviet forces. After demobilisation, 42,898 soldiers, of whom 30,000 were Lithuanians, had returned to Lithuania by 25 November 1946. In 1944, 63,000 men had been mobilised, 24,100 of whom had been taken to military commissariats by force. By 1 June 1945, an additional 45,000 were mobilised, of whom 20,462 were inducted by force. Altogether, 46,674 men were taken to military commissariats by force. After the Soviet-German war, the forced mass mobilisation was stopped. According to official data, throughout the entire period of the mobilisation, 108,378 people were drafted into the Red Army, 82,000 of whom were Lithuanians. From 15 July 1944 to 1 December 1945, 1,774 draft dodgers and 196 deserters were sentenced.